Investigation of the non-equilibrium state of strongly correlated materials by complementary ultrafast spectroscopy techniques. (15th March 2021) - Hedayat, H; Sayers, C J; Ceraso, A; van Wezel, J; Clark, S R; Dallera, C; Cerullo, G; Da Como, E; Carpene, E
Abstract: Photoinduced non-thermal phase transitions are new paradigms of exotic non-equilibrium physics of strongly correlated materials. An ultrashort optical pulse can drive the system to a new order through complex microscopic interactions that do not occur in the equilibrium state. Ultrafast spectroscopies are unique tools to reveal the underlying mechanisms of such transitions which lead to transient phases of matter. Yet, their individual specificities often do not provide an exhaustive picture of the physical problem. One effective solution to enhance their performance is the integration of different ultrafast techniques. This provides an opportunity to simultaneously probe physical phenomena from different perspectives while maintaining the same experimental conditions. In this context, we performed complementary experiments by combining time-resolved reflectivity and time and angle-resolved photoemission spectroscopy. We demonstrate the advantage of this combined approach by investigating the complex charge density wave (CDW) phase in 1 T -TiSe2 . Specifically, we show the key role of lattice degrees of freedom to establish and stabilize the CDW in this material.